Identification ofsuperior parents and crosses in potato (Solanum tuberosum) by combining abilityanaIysis* - LUTHRA, S K; SHARMA, P C; GOPAL, J (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 1998-2000 at Modipuram Uttar Pradesh to identify good general combiners and superior crosses in potato (So!anunl tuberosunl L.) based on conlbining ability analysis of 120 crosses produced in line x tester lnating design involving 24 felllale and 5 nlale parents. The results showed preponderance of additive and non-additive gene action in seedling and second clonal generation, respectively. Parents ~MS/90-512' and 'MS/91-1325' were good general combiners for tuber yield components in both the generations. Crosses 'JII857' x 'JN2231' (for tuber yield and general inlpression) and 'MS/89-1 095' x 'CP2366' (for tuber yield and dry Inatter) had positive and significant specific cOll1bining ability in both the generations. Progeny means and specific combining ability effects were associated with each other and also with heterosis for tuber yield. Identification of parents based on general combining ability and crosses based on progeny mean and specific combining ability would be a suitable strategy in potato breeding.